Crude Radix Aconiti Lateralis Preparata (Fuzi) with Glycyrrhiza Reduces Inflammation and Ventricular Remodeling in Mice through the TLR4/NF-κB Pathway. (20th October 2020) - Yan, Ping; Mao, Wen; Jin, Lushuai; Fang, Mingsun; Liu, Xia; Lang, Jiali; Jin, Lu; Cao, Beibei; Shou, Qiyang; Fu, Huiying
Abstract : Radix Aconiti Lateralis Preparata (Fuzi) is a traditional Chinese medicine. Its alkaloids are both cardiotonic and cardiotoxic; however, the underlying mechanisms are unclear. Compatibility testing and processing are the primary approaches used to reduce the toxicity of aconite preparations. The purpose of this study was to compare the effects of crude Fuzi (CFZ), CFZ combined with Glycyrrhiza (Gancao) (CFZ+GC), and prepared materials of CFZ (PFZ) on heart failure (HF) in C57BL/6J mice and explore the potential mechanisms of action of CFZ. Transverse aortic constriction (TAC) was used to generate the HF state, and CFZ (1.5 g·mL −1 ), PFZ (1.5 g·mL −1 ), or CFZ+GC (1.8 g·mL −1 ) was orally administered to the HF-induced mice daily. For the subsequent 8 weeks, hemodynamic indicators, ventricular pressure indices, and mass indices were evaluated, and histopathological imaging was performed. CFZ, CFZ+GC, and PFZ significantly improved left ventricular function and structure and reduced myocardial damage. CFZ+GC was more effective than CFZ and PFZ, whereas CFZ had higher toxicity than CFZ+GC and PFZ. CFZ and CFZ+GC attenuated ischemia-induced inflammatory responses and also inhibited Toll-like receptor-4 (TLR4) and nuclear factor kappa beta (NF- κ B) action in the heart. Moreover, mass spectrometry analysis revealed a decrease in the levels of toxic components of CFZ+GC, whereas those of the protective components were increased. This study suggested that GC reduces the toxicity and increases the efficacy of CFZ on HF induced by TAC. Furthermore, GC+CFZ reduces the risk of HF by ameliorating the inflammation response, which might be partially related to the inhibition of the TLR4/NF- κ B pathway.